COMMITTEE - INC 3 Nursing (UPT Penerbitan Universitas Jember, 2017)
Advisor : Ns. Lantin Sulistyorini, M.Kes. Ns. Wantiyah, M.Kep. Murtaqib, M.Kep. Ns. Rhondianto, M.Kep. Chief : Ns. Siswoyo., M.Kep. Vice Chief : Ns. Ahmad Rifai., M.S Secretary : Ns. Emi Wuri Wuryaningsih, M.Kep., Sp.Kep.J Achmad Satar, S.E., M.M. Finance Committee : Ns. Dini Kurniawati, M.Kep., Sp.Kep.Mat. R. Nur Rahmad, S.Sos. Secretariat Committee : Ns. John Hafan S, M.Kep., Sp.Kep.MB Latifa Aini Susumaningrum, M.Kep., Sp.Kom. Ns. Kushariyadi, M.Kep. Murni Hermawati, S, S.Th., M.Th. Ika Noviana, A. Md. Program Committee : Ns. Dodi Wijaya, M.Kep Ns. Dicky Endrian Kurniawan, M.Kep. Wara Bhakti Pratiwi, S. Si., M. Si. Scientific Committee : Ns. Nur Widayati, M.N Ns. Retno Purwandari, M.Kep. Ns. M. Zulfatul A’la., M.Kep. Ns. Kholid Rosyidi MN., MNS. Ns. Peni Perdani., M.Kep. Logistic and Accomodation Committee : Ns. Erti Ikhtiarini Dewi, M.Kep., Sp.Kep.J. Hanny Rasni, M.Kep. Ariestina Eka M., S. Sos. Publication and Documentation Committee : Ns. Alfid Tri Afandi, M. Kep. Ns. Enggal Hadi, M. Kep. Edi Pitaya, S. P Rosid Facility and Equipment Committe : Ns. Mulia Hakam., M.Kep., Sp.MB. Ns. Baskoro Setioputro. M. Kep. Pengki Susanto Fandi Ahmad, S. E. Sofyan Fakih Triyono Edi Sulamin